Exploration of How Health Anxiety and Media Exposure Predict Preventive Health Actions - Popescu, Andreea; Nikolova, Mariana; Nasrin, Sharmin (KMAN Counseling & Psychology Nexus, 2025)
This study aimed to investigate how health anxiety and media exposure predict engagement in preventive health actions during the COVID-19 pandemic. A correlational descriptive design was used with a sample of 459 adult participants from Bulgaria, selected based on the Morgan and Krejcie sample size table. Participants completed standardized self-report questionnaires, including the Preventive Health Behavior Checklist (PHBC), the Short Health Anxiety Inventory (SHAI), and the Media Exposure Scale for Health Information (MESH). Data were collected online and analyzed using SPSS-27. Pearson correlation coefficients were calculated to assess the relationships between the dependent variable (preventive health actions) and each independent variable (health anxiety and media exposure). Multiple linear regression analysis was conducted to evaluate the predictive power of the two independent variables on preventive behaviors. Descriptive results indicated high mean scores for preventive health actions (M = 63.27, SD = 8.41), moderate to high health anxiety (M = 38.52, SD = 7.66), and moderate media exposure (M = 29.84, SD = 5.73). Pearson correlations showed significant positive relationships between preventive health actions and both health anxiety (r = .47, p < .001) and media exposure (r = .38, p < .001). Regression analysis revealed that health anxiety (β = .41, p < .001) and media exposure (β = .28, p < .001) were both significant predictors of preventive health actions, jointly accounting for 29% of the variance (R² = .29, F(2, 456) = 92.61, p < .001). The findings highlight the important roles of psychological and informational factors in promoting health-protective behaviors. Both health anxiety and media exposure significantly influence individuals’ engagement in preventive actions, underscoring the need for balanced media messaging and supportive mental health strategies during public health crises.